Imagining the "New Father”: Fatherhood and Masculinity in Keluarga Cemara (2018) - Aulia Rahmawati; Catur Putri Kirana (ULTIMA Comm, 2023)
This study critically analyzes the representation of fatherhood and masculinity in the Indonesian film Keluarga Cemara (2018). It utilizes Norman Fairclough's framework for critical discourse analysis to examine how sociocultural norms and expectations shape the conceptualizations of fatherhood roles. The analysis revealed that conventional patriarchal values dictate fatherhood primarily through an economic lens, placing immense pressure on fathers as financial providers. However, the film's portrayal of the character Abah disrupts this dominant narrative by highlighting the importance of the father's emotional presence and involvement in children's lives, even when facing financial constraints. Abah's struggles expose the narrow definitions of masculinity and fatherhood perpetuated by society. His character illuminates the phenomenon of "father hunger" arising from emotional disconnection when paternal roles focus exclusively on being the breadwinner. This study argues that the film prompts a re-examination of outmoded fatherhood norms to address children's holistic developmental needs. This emphasizes the need for a more inclusive understanding of masculinity and fatherhood in the Indonesian society and culture. The analysis is situated within the specific sociocultural context of the film, highlighting the complex interplay between cinematic texts, discourse, and broader norms. It underscores cinema's potential to challenge engrained gender roles and catalyze progressive social change